Factors contributing to Strategic Decisions in Small and Medium-sized Enterprises - Singh, Nirmal (2008)
Strategic decision is being viewed as one of the important factor and the driving force in the field of strategic management. There seems to be quite a number of contributing variables towards the outcome of the decision. The standard measurement usually will be the measurement of the effectiveness. This study focuses on the development from two contributing independent variables, competitive intelligence and intuitive synthesis.